Two women - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women posing together. The woman on the left has her left arm around the second woman and her hand on the other woman's left hip. The woman on the right is wearing a striped shirt and has her right hand on the first woman's right shoulder. There are people partially visible in the background.